Adjustable hybrid diffractive/refractive achromatic lens - Valley, Pouria (Optical Society of America, 2011)
We demonstrate a variable focal length achromatic lens that consists of a flat liquid crystal diffractive lens and a pressure-controlled fluidic refractive lens. The diffractive lens is composed of a flat binary Fresnel zone structure and a thin liquid crystal layer, producing high efficiency and millisecond switching times while applying a low ac voltage input. The focusing power of the diffractive lens is adjusted by electrically modifying the sub-zones and re-establishing phase wrapping points. The refractive lens includes a fluid chamber with a flat glass surface and an opposing elastic polydimethylsiloxane (PDMS) membrane surface. Inserting fluid volume through a pump system into the clear aperture region alters the membrane curvature and adjusts the refractive lens’ focal position. Primary chromatic aberration is remarkably reduced through the coupling of the fluidic and diffractive lenses at selected focal lengths. Potential applications include miniature color imaging systems, medical and ophthalmic devices, or any design that utilizes variable focal length achromats.